Respons Hematologi Itik Pengging yang Diberi Tepung Daun Kelor (Moringa oleifera. Lam) Sebagai Imbuhan Pakan - Kasiyati, Kasiyati; Djaelani, Muhammad Anwar; Sunarno, Sunarno (Jurnal Veteriner, 2021)
Pengging ducks are one breed of Indonesia’s local duck has superior potential. This study was designed to evaluate the hematological parameters of  Pengging ducks fed Moringa leaf meal as a feed additive. The data were obtained from a total of 80 female Pengging ducks of 35 weeks old were assigned into a completely randomized design and each experimental unit consisted of 4 replications. The treatment group consisted of basal fed without added Moringa leaf meal (control), basal fed added with 2.5, 5, 7.5, and 10% Moringa leaf meal. Data analyzed using one-way ANOVA. The results showed that the addition of Moringa leaf meal gave same effect (P>0.05) on the number of erythrocytes, hemoglobin, hematocrit, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH). However, the mean corpuscular hemoglobin concentration (MCHC) increased (P<0,05) to 15.91% at 5% moringa leaf meal. The number of leukocytes was lower (P<0.05) by 42.01% at 7.5% moringa leaf meal. Leukocyte differentials, the ratio of H:L, and trombocytes did not significant difference (P>0.05) between treatments. In conclusion, the Moringa leaf meal as a feed additive did not change the hematological parameters and could be increasing the health status of layer Pengging ducks.